Investigation of structural and biomotoric features of young volleyball players and determining the position by disciriminant analysis - Kilic, I.; Binboga, M. (Annals of Ovidius University Constanta-Series Physical Education and Sport/Science, movement and health, 2012)
The aim of this study is to analyze structural and biomotoric features of male and female setter and smasher volleyball players in 15-17 age group. The study was carried out in Afyonkarahisar City Center; measurements were made on totally 113 volunteer volleyball players. There were 29 smashers and 15 setters from 5 male teams participated in Youth Group Volleyball Matches; while there were 49 smashers and 20 setters from 8 female teams. T-test was used for comparing young volleyball players` structural and biomotoric features according to sex and position. Relation between variables of structural and biomotoric features were determined by correlation analysis. On the other hand, discriminant analysis was carried out in order to classify players according to position in terms of biomotoric features and to determine the important/unimportant variables in this classification. At the end of the research, it was determined that flexibility values of setters were higher than smashers while smashers were better than setters in terms of other biomotoric features. There were found to be significant relation between biomotoric features (except flexibility) and height-weight. Additionally, in the classification of players s setter and smashers, the most significant variable for female players were found to be left hand grasping power and flexibility, while for male players the most significant variable was right hand grasping power.